Production of a nutritionally-improved and shelf- stable ready-to-consume Kunun gyada powder made from blends of rice, groundnut, sesame seed and germinated soybean - Musa, Halilu (2019)
Kunun gyada is a traditional Nigerian cereal porridge commonly made from rice flour and groundnut milk. It is not shelf stable and can only be kept for 12 to 24 hours without refrigeration. It has low protein content of 2.30 % and therefore needs improvement. The preparation of kunun gyada is time consuming and there are variations in its production process. Therefore, a novel way to improve on this product is to conduct research investigation to standardize the production process of kunun gyada, improve its nutritional composition especially protein content and shelf-life. Thus, the aim of this study was to produce a shelf-stable and ready-to-consume kunun gyada powder of high nutritional quality. Results obtained from germination of soybean from 0 to 72 hour showed that the germinated soybean has a moisture content ranging between 4.15 and 8.67 %, ash from 5.31 (control) to 5.78 % (dry wt. basis). Samples which had been germinated for 24 hour had the highest protein content of 32.01 % (dry wt. basis). Germination significantly (P≤0.05) decreased the crude fat from 26.18 to 18.02 % (dry wt. basis) while total carbohydrate content increased from 31.36 to 48.39 % (dry wt. basis). Essential and non-essential amino acids increased during germination, where histidine increased by 11.82 %, threonine 9.14 %, valine 9.84 %, methionine 7.24 %, and lysine had an increase of 61.11 % at 24 hour germination time. The fatty acid composition of non-germinated (control) and germinated soybean samples showed that linoleic acid was the most abundant unsaturated fatty acid and the relative percent ranged between 56.99 and 57.56 %. The predominant saturated fatty acids were palmitic acid from 11.48 to 11.91%, and stearic acid 3.76 to 3.92 %. Mineral analysis indicated that iron content ranged between 0.117 (control) to 0.155 mg/100 g (72 h), and calcium decreased significantly (P≤ 0.05) from 5.45 (control) to 1.23 mg/100 g (72 h). The magnesium content ranged between 10.37 (control) and 10.69 mg/100 g (72 h) and zinc between 0.098 (control) and 0.076 mg/100 g (72 h). Potassium increased from 41.97 mg/100 g in the non-germinated soybean to 46.33 mg/100 g (60 h), while phosphorous from 24.80 mg/100 g to 27.30 mg/100 g. Germination had a reducing effect on trypsin inhibitor activity, decreasing by nearly 50 % following germination for 72 hours (43.26 mg/g in non-germinated soybean). Results obtained show that the protein content of the ready-to-consume kunun gyada powder has significantly increased from 3.61 in control sample (KGP1) consisting of 40 % rice flour and 60 % groundnut milk to 14.44 % in a formulation comprising 60 % groundnut milk, 25 % rice flour and 15 % germinated soybean flour (KGP3), crude fat range between 14.23 in KGP1 and 24.97 % in a formulation comprising 60 % groundnut milk, 25 % rice flour, 10 % germinated soybean flour and 5 % roasted sesame flour (KGP5) and carbohydrate content reduced from 74.26 (KGP1) to 55.43 % in KGP5. Histidine increased by 285.7 %, threonine 304.8 %, valine 426.7 %, methionine by 400 % and lysine increased by 121.4 %, respectively. There was a significant decrease (P < 0.05) the in colour L* from 86.21 (control) to 72.36 % (KGP3). Calcium increased from 5.30 mg/100 g in the control (KGP1) to 6.43 mg/100 g dry ash (KGP4 = 60 % groundnut milk, 30 % rice flour, 5 % germinated soybean flour and 5 % roasted sesame flour), zinc from 0.08 to 0.27 mg/100 g (KGP4), iron from 0.18 mg/100g (KGP1) to 0.26 mg/100 g (KGP4), potassium from 31.02 mg/100 g (KGP1) to 33.43 mg/100 g in KGP3, magnesium 7.28 mg/100 g (control) to 8.56 mg/100 g in KGP3 and phosphorous 9.22 to 14.3 mg/100 g (KGP5), respectively. The peroxide value of freshly prepared samples of kunun gyada powder ranged between 0.19 (KGP3) and 0.47 mEq/kg (control). Reconstitution time range between 18.33 and 98.67 seconds. The product was scored high by panelist in all sensory attributes (colour, taste, texture, aroma and overall acceptability) evaluated. Results obtained for storage study show that the water activity (aw) ranged between 0.54 (KGP3) and 0.61 (KGP1) at the beginning of storage and 0.38 and 0.45 after 9 months. The colour of the product in terms of lightness (L*) remained unchanged. The peroxide value (PV) was never above 0.52 meq/kg after storage for 9 months. The thiobarbituric acid value (TBA) of the product was also low, and after storage, was 41 MAE/kg. Coliform, bacteria, yeasts and molds were not detected in the finished product during and after storage for 9 months. Results for sensory evaluation based on a 9-point Hedonic scale showed that reconstituted product KGP5 was scored higher compared to the other products with a score of 7.63. However, the panelists also indicated that the powder of KGP5 was slightly oily to the touch. Due to this, the KGP5 was modified to contain 5 % maltodextrin. The colour of the maltodextrin added product was significantly lighter (L* was 76.31%). The viscosity of the product also increased from 15.75 to 17.12 mPa.s. Addition of maltodextrin improved the product’s overall acceptability significantly from 2.72 to 3.89 based on a five-point Hedonic scale.